الشعر الحر بين العرب والملايويين: دراسة مقارنة: (Free Verse Poetry between Arab and Malay: A Comparative Study) - عدلي بن يعقوب; (Nurul Hidayah Binti Rosly), نور الهداية بنت روسلي (At-Tajdid - Intellectual Refereed Journal, 2025)
Free verse poetry represents a significant innovation in modern Arabic poetry, as Arabic poetry transitioned from imitation and suggestion to renewal in both form and content. Free verse poetry is one of the most important modern literary movements that has gained substantial attention in literary studies due to its role in transforming the course of Arabic poetry. Free verse first emerged in Europe and then influenced Arabic, Malay, and other literatures. Based on this context, this study investigates the emergence and development of free verse poetry in both Arab and Malay societies, presenting examples of free verse by four of its pioneers: Nazik al-Malaika, Badr Shakir al-Sayyab, Muhammad Yasin Makmur, and A. Latiff Mohidin. The study compares free verse in Arab and Malay poetry in terms of history, themes, and artistic techniques. This research uses both analytical and comparative methodologies, starting with the emergence and development of free verse, followed by a comparison of the similarities and parallels between Arabic and Malay free verse poems, highlighting the artistic creativity in both. The study concludes that free verse exists in both Arab and Malay countries and provides significant freedom of expression by not adhering to traditional poetic rules such as rhyme and meter. Keywords: Free verse, Nazik al-Malaika, Badr Shakir al-Sayyab, Muhammad Yasin Makmur, A. Latiff Mohidin.